2014
DOI: 10.1128/cvi.00638-14
|View full text |Cite|
|
Sign up to set email alerts
|

Highly Purified Mycobacterial Phosphatidylinositol Mannosides Drive Cell-Mediated Responses and Activate NKT Cells in Cattle

Abstract: M embers of the mycobacterial genus are renowned for their waxy, lipid-rich outer envelope. Under physiological conditions, this outer layer is likely to be the first point of contact between the bacterial cell and the host's immune system, and the outcome of this interaction is pivotal in the establishment of infection. One of the most important groups of membrane bound lipids consists of the phosphatidylinositol mannosides (PIMs). Interest in PIMs was stimulated since it was shown that phosphatidylinositol d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…NKT cells also recognize lipid ligands complexed with the non-MHC surface molecule, CD1d, and were also referred to as “CD1d-restricted” T-cells ( 20 ). CD1d is absent in cattle ( 21 ) but bovine T-cells co-expressing CD335 do recognize lipid ligands by a CD1d-independent mechanism ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NKT cells also recognize lipid ligands complexed with the non-MHC surface molecule, CD1d, and were also referred to as “CD1d-restricted” T-cells ( 20 ). CD1d is absent in cattle ( 21 ) but bovine T-cells co-expressing CD335 do recognize lipid ligands by a CD1d-independent mechanism ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that non-MHC-restricted lymphocytes were recruited to the lungs of calves following BHV-1 infection ( 7 ) but it was not determined whether these cells were conventional NK cells or non-conventional T-cells. It is not known if non-conventional T-cells may be recruited to bovine mucosal surfaces since previous studies of bovine non-conventional T-cells were limited to cells isolated from blood ( 12 , 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the comparison to PPD-A may not be appropriate in animals or regions where colonizing or sensitizing NTMs are only distantly or not at all related to M. avium [7]. Moreover, the sensitivity and specificity of the SIT and SICCT could be affected in MAP infected herds [48]. Therefore, our results suggest that PIMs generate a non-specific immune response that inhibits mycobacterial diagnostic test specificity when using complex antigen preparations.…”
Section: Discussionmentioning
confidence: 90%
“…Although the humoral PIM response is too unspecific for the implementation in diagnostic assays, the CD1 based T-cell response to lipid extracts of naturally infected MAP and MB infected animals is highly specific, and exclusively detected in infected animals [36]. Among these lipids, PIMs, and specifically AcPIM 6 , are recognized by CD3 receptors, resulting in natural killer T-cell activation and induced interferon gamma production in bovine lymphocytes [48]. This suggests that PIMs elicit a specific cell mediated immune response, and that PIMs could be suitable antigen candidates for novel (non-classical) T cell-based tests.…”
Section: Discussionmentioning
confidence: 99%
“…The chromatography was performed in a TLC chamber saturated with C/M 94:6. Afterwards, the TLC plate was stained with Hanessian's stain [92], baked for 1 min at 150 • C, and scanned at 300 dpi. Finally, the signal was quantified using the software LabImage 1D (Intas, Göttingen, Germany).…”
Section: Lipid Extraction and Quantitative Measurement Of The Cellulamentioning
confidence: 99%